If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(2b + -7) = 4(b + 10) Reorder the terms: 8(-7 + 2b) = 4(b + 10) (-7 * 8 + 2b * 8) = 4(b + 10) (-56 + 16b) = 4(b + 10) Reorder the terms: -56 + 16b = 4(10 + b) -56 + 16b = (10 * 4 + b * 4) -56 + 16b = (40 + 4b) Solving -56 + 16b = 40 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. -56 + 16b + -4b = 40 + 4b + -4b Combine like terms: 16b + -4b = 12b -56 + 12b = 40 + 4b + -4b Combine like terms: 4b + -4b = 0 -56 + 12b = 40 + 0 -56 + 12b = 40 Add '56' to each side of the equation. -56 + 56 + 12b = 40 + 56 Combine like terms: -56 + 56 = 0 0 + 12b = 40 + 56 12b = 40 + 56 Combine like terms: 40 + 56 = 96 12b = 96 Divide each side by '12'. b = 8 Simplifying b = 8
| 6x-3x-12= | | 1.04p=124.8 | | 2340=(n-2)180 | | h=5+27t-16t^2 | | -5=-1.60(4)+b | | 7x+19x+13x= | | x^2-y^2=100 | | 96=2(5x+3)+2(4x) | | -4x-27=7x+7 | | y-b=nyb | | x^3y^2+5x^2y-14x=0 | | 5(x+4)+(3x-5)= | | 208=2(5z+2)+2(4z+3) | | 68=.2(20x+50)+2 | | y=-1.60x+b | | -9x^2+35x-30=1-x | | 4y-0.9=5y | | 9(x+5)=6x+2 | | (2+y)(3y+7)=0 | | -3(-5x+2)= | | (8x+1)2+5=10 | | 3x^4+33x^3+90x^2=0 | | -5(4x-2)= | | a^(1/3)*a^(4/3) | | 4x-7x-13=-3x+7-13 | | (6x+2)(3x-5)=(9x-4)(2x+4) | | p^2p/p^-5 | | 2/3x-1=-1/3x-5 | | (2x^4+6y)(2x^4-6y)= | | 2(3x+3)=5(x-4) | | -3(x+5)=2-2x | | 12x^2+4x+15=0 |